EVALUASI PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) DI RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG - Vinidia Pertiwi; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Roemani Muhamadiyah Semarang Hospital is special type hospital grade “C”. As the hospital, the operational produces hazardous and toxic waste that its should be managed. The purpose of this study is to evaluate the hazardous and toxic waste management in Roemani Muhammadiyah Semarang Hospital according to Minister of Environment and Forestry Regulation No. 56 in 2015 about regulation of hazardous and toxic waste management in health service. Type of reseach is descriptive method with qualitative approach with primary and secondary data. Primary data obtained using the technique of indepth interview against the selected informants and observartin, the secondary data obtained from a review of the documents. Based on this research hazardous and toxic waste come from 7 hospitalcare with various types of hazardous and toxic waste such syringes, infusion hoses, tissue and fluids body. The average amount of hazardous and toxic waste generated as much as 1672,1 kg/month and managed by third-party. Overall medical waste management in Roemani Muhammadiyah Semarang Hospital not yet appropriate the regulation of hazardous waste management in health service according to regulation. There are some missmatch at each process of management, such as mistake in warehousing, reduction process not yet applied in medical waste management, hazardous and toxic waste disposal in the inpatient room is under standard, reduction process not yet applied in medical waste management, unoptimal policies and operating procedur, mistake in stroge and transportation.